Efektifitas pelatihan manajemen marah untuk mengurangi agresivitas pada siswa SMAN 8 Makassar - Emiliati, Fenny (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
The Purpose of this study to determine the effectiveness of anger management training to reduce student’s aggressiveness at SMAN 8 Makassar. This study uses a quantitative approach experimental of True Experimental Design. The population in this study were 80 students who have a high level of aggressiveness dan sample selected by technique simple random sampling as many as 40 students which is them divided 20 students for the experimental group and 20 students for the control group. Training of anger management is carried out as much as 6 session with 7 time meetings. Data collection techniques gained through scale, questionnaire and observation. Data were analyzed using descriptive statistical analysis and hypothesis testing using inferential statistical analysis parametric t-test. The result showed that there is difference significance student’s level aggressiveness before and after received anger management training (p = 0,000 < α = 0,05). Based on result, the study concluded that anger management training can reduce the student’s level aggressiveness at SMAN 8 Makassar.